Novel mutation sites in the Bubaline MC1R gene (Journal of Advanced Veterinary and Animal Research, 2026)
Objective: Buffalo (Bubalus bubalis) is an important livestock species raised for meat, milk, and draught purposes. In Indonesia, buffaloes with rare coat colors (e.g., white, striped) hold cultural significance, especially in Toraja funeral traditions. This study aimed to identify mutation sites in the exon 1 region (822 bp) of the Melanocortin 1 Receptor (MC1R) gene in buffaloes using forward sequencing. Materials and Methods: Four Toraya buffaloes (1 white, 2 striped, and 1 black) and two black Murrah buffaloes were used as experimental animals. In addition, seven MC1R gene sequences from different buffalo breeds (Murrah × Dehong (light grey), Dehong (white and dark grey), Murrah (black), Jafarabadi (black), and Surti (brown)) were obtained from the NCBI database for comparative analysis. Results: A total of five nucleotide variation sites were identified in the experimental animals, including three novel mutations (c.26M, c.49Y, and c.50R) and two previously reported mutations (c.170R and c.244K). Among these, c.50R was identified as a synonymous mutation, while the remaining mutations were non-synonymous and predicted to affect the amino acid sequence of the MC1R protein. Notably, all three novel mutation sites were consistently present in all studied Toraya and Murrah buffaloes, suggesting shared genetic variants across phenotypically distinct populations. Structural prediction analysis indicated that these mutations could potentially alter the conformation and function of the MC1R protein. Conclusion: The identification of three novel mutations in the MC1R gene enhances our understanding of coat color variation and genetic diversity in Indonesian buffalo populations, particularly those of cultural and economic significance.J. Adv. Vet. Anim. Res., 12(4): 1345–1353, December 2025http://doi.org/10.5455/javar.2025.l994